PROPOSED VALUE ADDED AND MARKETING STRATEGY IMPROVEMENT FOR INDONESIAN SPECIALTY COFFEE (The Indonesian Journal of Business Administration, 2019)
Indonesia as a country that located in the coffee belt, produce coffee with various characteristics. High number of coffee production in Indonesia is not comparable with the income that the roastery get because Indonesia consumption of coffee still dominated by commercial coffee or low-quality coffee. To increase the income of coffee roastery can be done with increase the consumption of high-quality coffee or what it is called specialty coffee. But then, consumption of Indonesian specialty coffee is still low. Objectives of the research is to collect the related information for the Indonesian specialty coffee roastery, taste preference of Indonesian coffee drinker, also to find the right marketing strategy for roastery to increase the consumption of specialty coffee in Indonesia. The methods used in this research are blind cupping as the primary data and literature review as secondary data. As solution of the problem, marketing strategy programs that are used, include product development, allow and encourage the stakeholders to collaborate in creating a value experience to involve the customer. Consumers experience will stimulate their knowledge and interest in Indonesian specialty coffee. Collaboration between stakeholders also expected to increase the knowledge among the coffee roastery.Keywords: Consumer Knowledge, Coffee Flavor, Indonesian Specialty Coffee, Marketing Mix Strategy, and Product Development.